2022
DOI: 10.1108/ijssp-08-2021-0200
|View full text |Cite
|
Sign up to set email alerts
|

Home-based work or non-home-based work? Factors influencing work choices of women in the informal sector

Abstract: PurposeThe purpose of the study is to determine the factors influencing the job choices of Indian women working in the informal manufacturing sector. The informal sector has always played a significant role in emerging and developing countries. This study investigates the effect of social cultural norms influencing women informal workers in the manufacturing sector to participate in home-based work (HBW) or non-home-based work (non-HBW) .Design/methodology/approachBoth Quantitative and Qualitative methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Male business owners, relative to female owners, demonstrate a lower probability of engaging in wholesale and retail businesses, particularly pronounced in non-HBEs. This gender preference for home-based wholesale and retail trade might stem from the flexibility it offers in balancing household duties and labour market activities [ 31 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Male business owners, relative to female owners, demonstrate a lower probability of engaging in wholesale and retail businesses, particularly pronounced in non-HBEs. This gender preference for home-based wholesale and retail trade might stem from the flexibility it offers in balancing household duties and labour market activities [ 31 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…based wholesale and retail trade might stem from the flexibility it offers in balancing household duties and labour market activities [31,45,46]. Geopolitical disparities notably influence the likelihood of operating HBEs and non-HBEs in wholesale and retail sectors.…”
Section: Plos Onementioning
confidence: 99%
“…Having less choice when it comes to work matters because unequal perceptions of choice can both signify and perpetuate stalled gender progress (Gerson, 2009). Further, research has shown that gender expectations, specifically, make a difference for individuals' choices around how, when and where they work (Blair-Loy, 2005;Dadheech and Sharma, 2023;Hochschild, 2003). Therefore, if there are gendered differences in choice perceptions, it can both signify and perpetuate gender inequalities when it comes to work (and work-life balance).…”
Section: Discussionmentioning
confidence: 99%
“…Though our research raises additional questions that would benefit from further investigation, our current findings have implications for policies meant to advance gender equity at work. For working women, policies that relieve some of the burden of domestic responsibilities (such as universal childcare) could help expand perceptions of choice, thus reducing the risk that women's progress in the workplace is stalled due to perceptions that they don't have much choice given the combination of gender expectations and domestic responsibilities (Blair-Loy, 2005; Dadheech and Sharma, 2023). More progressive leave policies could benefit men as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation